Illness perceptions and health outcomes in HS. (1st February 2019) - Pavon Blanco, A.; Turner, M.A.; Petrof, G.; Weinman, J.
Summary: Hidradenitis Suppurativa (HS) is a chronic skin condition that affects between 1 and 2% of the European population. It is caused by inflammation of the hair follicles and sweat glands which results in painful and unpleasant‐smelling swellings under the skin in the armpits, groins, genitals and under the breasts. HS has been associated with depression, anxiety and impaired quality of life (QoL). Previous studies have linked these effects with the severity of the disease as assessed by the clinician, but it has not been investigated whether health outcomes (depression, anxiety and QoL) are related to the patient's beliefs about their condition (illness perception). In this study from a specialised HS clinic in a large UK hospital, dermatologists collaborated with psychologists to establish for the first time, the relationships between illness perceptions and health outcomes. Particularly, they wanted to investigate whether health outcomes were more strongly related to the severity of the disease or to the patient's perceptions of HS. They used routinely collected data from patients' self‐report questionnaires assessing illness perceptions (BIPQ), depression (PHQ‐2), anxiety (GAD‐2) and impaired quality of life (DLQI) from an initiative called IMPARTS (Integrating Mental and Physical Healthcare: Research Training and Services). IMPARTS has been introduced into routine clinical practice across several specialties in some London hospitals and the collected data can be used for research purposes with the appropriate approval and consent. This study involved 211 patients aged 17 to 71 with mild, moderate and severe HS. Self‐reports showed significant levels of depression, anxiety and impaired QoL which were more strongly associated with illness perceptions compared to disease severity. The authors concluded that routine assessment of patients' perceptions of their condition, and interventions aimed to address negative and unhelpful beliefs and emotions, could improve health outcomes in HS.